Wireless network design for the Tocuyo and Carora Nuclei (Publicaciones en Ciencias y Tecnología, 2008)
In this research a radio network is designed that allows to provide services of Voice IP, data and Internet connection to El Tocuyo and Carora external UCLA campuses at a greater speed. The network is designed taking into account new technologies and methods of wireless connections to calculate the points to connect, height of the antennas and types of antennas among other things. Currently, a Frame Relay network connection between the main campus and these two sites is in operation but at a speed of 256kbps, causing many required services to be left out due to the low combined speed and high maintenance costs. This work proposes the equipment to be used, the design and specifications of the wireless link, in the aim of enhancing speed and quality of service and at the same time, eliminating the need of a Frame Relay service contractor.
Keywords: Radio networks; network security; network sevices